KORELASI KADAR LEMAK DAN LAKTOSA DENGAN BERAT JENIS SUSU SAPI FRIESIAN HOLSTEIN DI KECAMATAN NGABLAK KABUPATEN MAGELANG - Danes Suhendra; Widitya Tri Nugraha; Yosephine L. R. E. Nugraheni; Lilis Hartati (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2020)
Milk density and fat content are used as indicators of milk production from dairy farmer by Milk Proccessing Industry (MPI). Some MPI determines the price of milk based on fat and milk lactose content. This research was aimed to study the correlation of fat content, lactose content, and milk density. The material used were 90 of lactation FH cows in the II – III lactation periode and month of lactation are 2 – 3. The analysis method used was simple linear correlation regresion. The results showed that during increased milk fat and lactose contents, will increased milk density. Fat and lactose content are significantly correlated with milk density (P<0.01). The overall calculation shows that there was a relationship between fat content and lactose content to milk density, each 70.8 and 68.7%. Fat content with milk density, and lactose content with milk density showed a strong positive correlations. In conclusion, there was a correlation between fat content and lactose content with milk density. The correlation of fat content and lactose content with milk density were the higher fat and lactose content, higher milk density.